Risk Factors Increased Levels of Serum Glutamate Oxcaloacetate Transferase (SGOT) and Serum Glutamate Pyruvate Transferase (Sgpt) in The Community in The District North Konawe - Nawir, Hasan; Tasnim, Tasnim; Munir, Sanihu (Magister Kesehatan Universitas Mandala Waluya, 2023)
Background: Based on data on the number of blood chemistry tests at the North Konawe Regency Regional General Hospital in 2019 amounted to 1,519 cases, an increase in 2020, namely 1,659 cases and an increase in 2020 to 2,264 cases. The purpose of the study was to analyze the risk factors for increasing SGOT and SGPT levels in the People of North Konawe Regency. Methods: This study used the Case Control Studyapproach. The population numbered 48 people. The Study Sample totaled 23 SGOT and SGPT improvement samples and 23 control samples. The sample technique in this study is Simple Random Sampling. The data was processed using the Data Normality Test (Kolmogrov Smirnov Test) Odds Ratio Test and logistic regression Result: The results showed that smoking or 2,769, alcohol consumption OR 6.476 and consumption of or drugs OR 5.312 against the increase in serum glutamate pyruvate transferase levels (SGPT) in The Community of North Konawe District. Regression tests showed that alcohol consumption was the most at-risk factor for increased levels of serum glutamate oxaloacetictransferase (SGOT) and serum glutamate pyruvate transferase (SGPT) in the People of North Konawe Regency. Conclusion: Research shows that occupation, smoking habits, alcohol consumption and drug consumption are risk factors for increased levels of serum glutamate oxaloacetictransferase (SGOT) and serum glutamate pyruvate transferase (SGPT) in the people of North Konawe Regency.